Clinical Significance of Shared T Cell Epitope Analysis in Early De Novo Donor-Specific Anti-HLA Antibody Production After Kidney Transplantation and Comparison With Shared B cell Epitope Analysis - Tomosugi, Toshihide; Iwasaki, Kenta; Sakamoto, Shintaro; Niemann, Matthias; Spierings, Eric; Nahara, Isao; Futamura, Kenta; Okada, Manabu; Hiramitsu, Takahisa; Takeda, Asami; Goto, Norihiko; Narumi, Shunji; et al. (Frontiers in Immunology, 2021)
In pre-sensitizing events, immunological memory is mainly created via indirect allorecognition where CD4+ T cells recognize foreign peptides in the context of self-HLA class II (pHLA) presented on antigen-presenting cells. This recognition makes it possible for naive CD4+ T-helper cells to differentiate into memory cells, resulting in the creation of further antibody memory. These responses contribute to effective secretion of donor-specific anti-HLA antibodies (DSA) after second encounters with the same peptide. Preformed donor-reactive CD4+ memory T cells may induce early immune responses after transplantation; however, the tools to evaluate them are limited. This study evaluated shared T cell epitopes (TEs) between the pre-sensitizing and donor HLA using an in silico assay, an alternative to estimate donor-reactive CD4+ memory T cells before transplantation. In 578 living donor kidney transplants without preformed DSA, 69 patients had anti-HLA antibodies before transplantation. Of them, 40 had shared TEs and were estimated to have donor-reactive CD4+ memory T cells. De novo DSA formation in the early phase was significantly higher in the shared TE-positive group than in the anti-HLA antibody- and shared TE-negative groups (p=0.001 and p=0.02, respectively). In conclusion, evaluation of shared TEs for estimating preformed donor-reactive CD4+ memory T cells may help predict the risk of early de novo DSA formation after kidney transplantation.